2004
DOI: 10.1016/j.ejvs.2004.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Neoreflux After Correctly Performed Ligation of the Saphenofemoral Junction. A Randomized Trial

Abstract: Recurrent reflux in the groin was reduced by over sewing the ligated SFJ in patients having varicose vein surgery. This adds weight to the theory of neovascularisation as a cause of recurrent veins and offers a means to reduce clinical recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 26 publications
1
38
0
12
Order By: Relevance
“…[23][24][25] Attempts to prevent recurrences in the groin by inserting diverse sorts of barriers over the ligated SFJ were disappointing [26][27][28][29] ; mechanical barriers either moderately reduced reflux recurrence rate in the groin in some studies or were ineffective in others, but in all they did not preclude development of recurrent reflux. Some authors expressed the opinion that recurrent reflux in varicose vein disease was unavoidable, no matter how careful and painstaking the primary procedure might be, 28,30 and postulated that some unspecified hemodynamic factors might be responsible for recurrences. 31,32 The Hemodynamic Paradox A recent article dealt with that issue.…”
Section: Tendency Of Varicose Veins To Recurmentioning
confidence: 99%
“…[23][24][25] Attempts to prevent recurrences in the groin by inserting diverse sorts of barriers over the ligated SFJ were disappointing [26][27][28][29] ; mechanical barriers either moderately reduced reflux recurrence rate in the groin in some studies or were ineffective in others, but in all they did not preclude development of recurrent reflux. Some authors expressed the opinion that recurrent reflux in varicose vein disease was unavoidable, no matter how careful and painstaking the primary procedure might be, 28,30 and postulated that some unspecified hemodynamic factors might be responsible for recurrences. 31,32 The Hemodynamic Paradox A recent article dealt with that issue.…”
Section: Tendency Of Varicose Veins To Recurmentioning
confidence: 99%
“…26 These new blood vessels are found relatively frequently, even after correct functional ligation. Neovascularization has been reported to account for 8% to 60% of RVV 10,18,[40][41][42][43] and is the most common cause of recurrence, together with the development of varicose veins attributable to disease progression in many studies. 5,9,10,24,44,45 RVV secondary to neovascularization seem to be more common after open surgery than endovenous treatment or sclerotherapy.…”
Section: Disease Progressionmentioning
confidence: 99%
“…It is thought that neovascularization first develops months or even years after the initial operation. 50 It may be induced by diffusible angiogenic factors 18 released from the surrounding tissues. Physical factors that have been implicated include the type of suture material used to ligate the GSV stump, exposure to free stump endothelium, 51 hemodynamic effects, 52 operative trauma, and thrombosis 53 (Fig 2).…”
Section: Disease Progressionmentioning
confidence: 99%
“…23 In view of the crucial role of the endothelium, some authors have attempted to mitigate neovascularization by inverting the free endothelial border of the ligated GSV stump with a running suture. Frings et al 24 reported a reduction of DUS-diagnosed recurrence after 2 years, from 11% to 3% in 152 limbs. Haas et al, 25 however, could not reproduce these results.…”
Section: Discussionmentioning
confidence: 97%